Edge coating glue for lithium battery positive plate, preparation method, application and lithium ion battery
By forming a high cross-linking density network structure with a main chain polymer containing hydroxyl groups and an isocyanate cross-linking agent, combined with ceramic particles, the problems of insufficient interface adhesion, thermal stability and electrochemical performance of PVDF edge coating glue are solved, and high-performance edge coating of lithium-ion battery positive electrodes is achieved.
Patent Information
- Application Number
- CN202510793967.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-09-19
AI Technical Summary
The existing PVDF glue coating material for the positive electrode of lithium-ion batteries has deficiencies in interface adhesion, thermal stability and electrochemical performance, which affects the safety and reliability of the battery.
A main chain polymer containing hydroxyl groups and an isocyanate crosslinker are used to form a three-dimensional network structure with a high crosslinking density. Combined with ceramic particles, the component ratio is optimized to improve the adhesion, mechanical strength and electrolyte resistance of the coating. The coating uniformity is ensured by the step-by-step temperature control technology.
It significantly improves the adhesion, mechanical strength and electrolyte resistance of the edge coating of the lithium-ion battery positive electrode, reduces the risk of decomposition of the coating in high temperature environments, and enhances the safety and reliability of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion battery edge coating, and in particular to an edge coating glue for a lithium battery positive electrode sheet, a preparation method, an application, and a lithium-ion battery. Background Art
[0002] As a storage device with high energy density, long cycle life and low self-discharge rate, lithium-ion batteries are widely used in consumer electronics, power batteries and energy storage. In the preparation process of lithium-ion batteries, in order to improve the safety and reliability of battery cells, positive electrode edge coating glue technology has gradually been applied to the electrode coating process. This technology prevents the electrode active material from peeling off during slicing, lamination or winding by coating a layer of adhesive material (i.e. edge coating glue) on the edge of the electrode, and improves the mechanical strength and structural stability of the electrode. The edge coating glue commonly used in the market currently uses PVDF (polyvinylidene fluoride) as the main binder, which has good electrolyte resistance, but has the following problems: 1. Limited interfacial adhesion with cathode materials Although PVDF has good adhesion, its interfacial bonding with certain positive electrode active materials (such as high-nickel NCM, NCA, etc.) is weak. Especially during battery cycling or high-temperature environments, interfacial cracking or falling off is prone to occur, posing certain safety hazards and affecting the long-term protective effect of the edge coating.
[0003] 2. Insufficient thermal stability PVDF is prone to thermal decomposition or softening under high temperature conditions, causing the edge coating to lose mechanical strength during battery thermal runaway or high-temperature cycling, thereby weakening the protective effect on the edge of the positive electrode.
[0004] 3. Potential impact on electrochemical performance PVDF may react with the electrolyte in the battery, especially at high temperatures, to produce fluorinated byproducts, which can lead to increased battery impedance, gas evolution, and capacity attenuation.
[0005] Based on the above disadvantages, there is an urgent need to develop new side coating materials and processes that can overcome the shortcomings of PVDF side coating, so as to achieve higher interfacial bonding strength and better thermal stability, thereby meeting the needs of the next generation of high-performance lithium-ion batteries.
[0006] In view of this, this patent application is filed. Summary of the Invention
[0007] In order to solve the above-mentioned problems existing in using PVDF as an edge coating adhesive, the present invention provides an edge coating adhesive for a lithium battery positive electrode sheet, and also provides a preparation method and application thereof.
[0008] The present invention is achieved through the following technical solutions: The first object of the present invention is to provide an edge coating adhesive for a lithium battery positive electrode sheet, comprising the following components: a main chain polymer, a cross-linking agent, a catalyst, a toughening agent, ceramic particles, and a solvent; The main chain polymer is a polymer containing a hydroxyl group, and the cross-linking agent is an isocyanate cross-linking agent.
[0009] The edge coating glue provided by the present invention is a polymer system based on hydroxyl-isocyanate cross-linking reaction. By optimizing the main chain polymer and cross-linking agent, the adhesion, high-temperature mechanical strength, electrolyte resistance and coating uniformity of the coating are significantly improved, providing an innovative solution for high-performance edge coating of lithium-ion battery positive electrodes.
[0010] Specifically, the hydroxyl-containing polymer selected in this invention forms strong hydrogen and covalent bonds with the isocyanate crosslinker, creating a high-density three-dimensional network during the crosslinking process. This significantly improves the coating's adhesion and mechanical strength, resists thermal decomposition or softening even at high temperatures (150-160°C), and enhances the coating's electrolyte resistance. Furthermore, a certain amount of hydroxyl groups remain on the crosslinked polymer surface, which can form strong hydrogen bonds with the surface oxide layer of the positive electrode current collector (such as aluminum foil), further strengthening the adhesion between the edge coating and the current collector. This effectively prevents edge coating shedding caused by thermal cycling, chemical corrosion, or mechanical stress, significantly improving adhesion. The toughening agent enhances the coating's toughness and mechanical stress resistance, particularly addressing the problem of edge coating breakage and delamination during use. The introduction of ceramic particles provides the coating with excellent heat resistance, electrolyte resistance, and insulation properties, synergistically enhancing thermal stability with the polymer, crosslinker, and toughening agent. The low viscosity ensures uniform coating.
[0011] As a preferred design, the mass ratio of the main chain polymer, cross-linking agent, catalyst, toughening agent, ceramic particles, and solvent is (20-40): (5~15): (0.1~0.5): (1~5): (2~10): (40~60).
[0012] The present invention rationally designs the mass proportion of each component, specifically: The main chain polymer content is set at 20-40% by weight. This ratio ensures that the coating formed after the cross-linking reaction has good mechanical strength and flexibility, while also providing high adhesion for the side coating. If the main chain polymer content is too low, the coating will lack mechanical strength, while if the content is too high, it may increase the brittleness of the coating and affect uniformity.
[0013] The mass ratio of the cross-linking agent is set at 5-15: This ratio is to ensure the strength and adhesion of the coating while avoiding the problem of the coating being too hard and easy to crack due to excessive cross-linking density.
[0014] The mass ratio of the catalyst is set to 0.1-0.5: The optimization of the catalyst content can ensure rapid cross-linking and curing, and complete sufficient cross-linking density within the set curing time (less than or equal to 60 seconds). On the basis of process efficiency, it avoids the side reaction problem caused by excessive catalyst and improves the mechanical strength and bonding performance of the coating.
[0015] The mass ratio of the toughening agent is set to 1-5: By optimizing the amount of toughening agent added, the toughness and elastic modulus of the coating are optimized, the problem of coating cracking caused by stress concentration during the curing process is alleviated, and the toughness and mechanical stress resistance of the coating are improved, especially solving the problem of breakage and peeling of the edge coating during use.
[0016] The mass ratio of ceramic particles is set to 2-10: The introduction of ceramic particles provides the coating with excellent heat resistance, electrolyte resistance and insulation properties. The high dielectric constant and low conductivity of ceramic particles help to improve the electrical insulation of the coating, thereby effectively preventing short circuit problems caused by local current leakage in lithium-ion batteries under extreme working conditions. At the same time, ceramic particles form a microscopic reinforcement structure through uniform dispersion, which improves the mechanical strength and dimensional stability of the coating. However, too low a content of ceramic particles may lead to insufficient coating performance, including reduced heat resistance, mechanical strength and insulation properties; while too high a content will worsen the rheological properties of the slurry, increase the difficulty of coating, and affect coating uniformity and surface quality.
[0017] The solvent content is set to ensure that the slurry has an appropriate viscosity, enabling uniform coating while avoiding bubbles or sedimentation during the coating process.
[0018] Compared with the conventional hydroxyl-isocyanate cross-linking reaction polymer system, the present invention increases the ratio of the main chain polymer to the cross-linking agent, increases the cross-linking density, improves the coating adhesion and electrolyte resistance, and reduces the content of the catalyst and toughening agent, reduces side reactions and improves the stability of the system, so as to be better applied to the side coating field of lithium-ion batteries and solve the technical difficulties in the use of side coating.
[0019] As a preferred design, the main chain polymer is a mixture of one or more of polytetramethylene ether, polyethylene glycol, polypropylene glycol, polytetramethylene glycol ether, terpolymer polyether, polypropylene oxide, polyethylene oxide, polycaprolactone polyol, polyadipic acid-ethylene glycol polyol, polyethylene oxide, and polytetramethylene oxide.
[0020] As a preferred design, the cross-linking agent is a mixture of one or more of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, dodecahydrotoluene diisocyanate, 1,4-butanediisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexyl diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, and PAPI.
[0021] As a preferred design, the catalyst is any one of dibutyltin dilaurate, zinc octoate, zinc dilaurate, zinc acetylacetonate, tetrabutyl titanate, bismuth trilaurate, zirconium acetylacetonate, triethylenediamine, triethylenediamine, N-methylimidazole, triethyl phosphate, potassium formate, sodium acetate, and bismuth-zinc composite catalyst.
[0022] And / or, the toughening agent is any one of SR610 (amine modified liquid rubber), ATBN (aminated liquid nitrile rubber), CTBN (carboxylated liquid nitrile rubber), carboxylated liquid nitrile rubber (Chemigum N967), and aminated liquid nitrile rubber (Hypro 1300X31).
[0023] As a preferred design, the ceramic particles are boehmite particles, and the D50 of the particles is 0.5-5 μm; And / or, the solvent is N-methylpyrrolidone.
[0024] A second object of the present invention is to provide a method for preparing the edge coating glue for the lithium battery positive electrode sheet as described in any one of the above, comprising the following steps: (1) Mix the main chain polymer and solvent according to the ratio and stir evenly; (2) adding a cross-linking agent to the product of step (1) and stirring evenly; (3) Adding a catalyst, a toughening agent, and ceramic particles to the product of step (2) and stirring evenly; (4) Mixing and homogenization.
[0025] As a preferred design, the dispersion speed during the mixing and homogenization in step (4) is controlled at 3000-5000 rpm and lasts for 5-20 minutes.
[0026] The third object of the present invention is to provide an application of the edge coating glue for lithium battery positive electrode sheets as described in any one of the above items, which is used to coat the edges of lithium battery positive electrode sheets, wherein the coating process comprises: uniformly coating the slurry on the edges of the positive electrode sheets; transferring the coated electrode sheets to a hot air circulation oven; Heating step by step: first cure at 60℃-80℃, then heat to curing temperature 150℃-160℃, curing time is less than or equal to 60 seconds.
[0027] In the present invention, when the above-mentioned edge coating glue is applied to the preparation of lithium battery positive electrode sheets, it is considered that during the cross-linking reaction and curing process, if the solvent evaporates too quickly or is unevenly distributed, it may cause microbubbles to be generated inside the coating, thereby reducing the uniformity and adhesion of the coating. In order to overcome this technical problem, the present invention adopts a step-by-step temperature control technology, that is, the solvent is evaporated at a low temperature in the initial stage of curing (60°C-80°C), and then the temperature is gradually increased to the cross-linking reaction temperature (150°C-160°C) to ensure that the solvent volatilization rate inside and outside the coating is consistent to prevent the generation of bubbles.
[0028] Accordingly, to avoid insufficient cross-linking reaction rates that could lead to insufficient coating strength and reduced adhesion in the side-coated area, the present invention optimizes the catalyst dosage and distribution in the side-coating adhesive composition design. High-efficiency catalysts (such as dibutyltin dilaurate) are selected to accelerate the cross-linking reaction, achieving sufficient cross-linking density within the set curing time (60 seconds), thereby improving the coating's mechanical strength and adhesion. However, during the rapid curing process, differences in thermal expansion coefficients can cause stress concentration, leading to cracking or shedding of the coating. To better accommodate the rapid curing process, the present invention mitigates the cracking caused by stress concentration during the curing process by optimizing the coating's toughness and elastic modulus through the rational design of a toughening agent. Therefore, by comprehensively considering the advantages and disadvantages of the side-coating adhesive polymer system and the curing process during the coating process, the present invention achieves a side-coating adhesive and coating process with optimal overall performance in terms of adhesion, mechanical strength, electrolyte resistance, electrochemical performance, and coating uniformity.
[0029] As a preferred design, before coating, the edge coating slurry is vacuum degassed: the slurry is treated in a vacuum degasser for 15 to 30 minutes with the pressure controlled at -0.1 to -0.2 MPa to remove bubbles in the slurry; And / or, the positive electrode sheet is subjected to surface pretreatment before coating, wherein the surface pretreatment is surface roughening or plasma treatment. The positive electrode sheet pretreatment is used to enhance the adhesion and durability between the coating and the substrate.
[0030] A fourth object of the present invention is to provide a lithium-ion battery, which uses any of the above-mentioned edge coating glues to coat the positive electrode sheet.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention uses a hydroxyl-containing main chain polymer and an isocyanate crosslinker to generate a coating structure with a high-density three-dimensional cross-linked network. This network structure has both high strength and toughness, and a certain amount of hydroxyl groups are still retained on the surface, which can form hydrogen bonds with the oxide on the surface of the positive electrode current collector, significantly enhancing the adhesion of the side coating. At the same time, the toughening agent in the polymer system improves the toughness and mechanical stress resistance of the coating, especially solving the problem of breakage and peeling of the side coating during use; and the introduction of ceramic particles provides the coating with excellent heat resistance, electrolyte resistance and insulation properties, and synergistically enhances thermal stability with the polymer, crosslinker and toughening agent. In addition, the low viscosity of the side coating of the present invention ensures the uniformity of the coating.
[0032] 2. The present invention carries out a cross-linking reaction during the coating process, which can be completed in a very short time (within 60 seconds), thereby avoiding the long drying of the PVDF edge coating during the coating process and avoiding the difficulty of adjusting the production line due to incompatibility with the positive electrode coating process. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with examples. The illustrative embodiments of the present invention and their descriptions are only used to explain the present invention and are not intended to limit the present invention.
[0034] Example 1: Raw material composition: Main chain polymer: polytetrahydrofuran (PTHF, molecular weight 1000): 25 parts by mass; polyethylene glycol (PEG, molecular weight 2000): 10 parts by mass; Cross-linking agent: isophorone diisocyanate (IPDI): 10 parts by mass; Catalyst: dibutyltin dilaurate (DBTL): 0.3 parts by mass; Toughening agent: amine-modified liquid rubber (SR610, Arkema): 3 parts by mass; Ceramic particles: boehmite particles (D50 = 0.8 μm, Qixian New Materials): 6 parts by mass; Solvent: N-methylpyrrolidone (NMP): 35 parts by mass.
[0035] Preparation process of edge coating: Prepare the mixture: Dissolve PTHF and PEG in NMP and stir at room temperature for 30 minutes until homogeneous. Slowly add IPDI and stir for 15 minutes until homogeneous. Add DBTL catalyst, SR610, and boehmite particles and stir for 30 minutes until homogeneous.
[0036] Homogenization treatment: Use high shear equipment to disperse at 4000 rpm for 15 minutes, and control the particle uniformity at D90 ≤ 5 μm.
[0037] Coating process on the positive electrode sheet: Degassing: vacuum degassing for 20 minutes (-0.1 MPa).
[0038] Coating and curing: The mixed slurry was evenly coated on the edge of the positive electrode sheet with a coating thickness of 15 μm; first kept at 60°C for 10 seconds, and then cured in a hot air circulation oven at 150°C for 40 seconds.
[0039] Example 2: Raw material composition: Main chain polymer: polytetrahydrofuran (PTHF, molecular weight 2000): 25 parts by mass; block polyether (PEG-PPG-PEG, molecular weight 1500): 10 parts by mass; Crosslinking agent: 1,6-hexamethylene diisocyanate (HDI): 14.8 parts by mass; Catalyst: triethylamine (TEA): 0.2 parts by mass; Toughening agent: carboxylated liquid nitrile rubber (Chemigum N967, Goodyear): 3 parts by mass; Ceramic particles: boehmite particles (D50 = 1 μm, Qixian New Materials): 5 parts by mass; Solvent: NMP: 42 parts by mass.
[0040] Preparation process of edge coating: Prepare the mixture: Dissolve PTHF and PEG-PPG-PEG in NMP and stir for 30 minutes. Slowly add HDI and stir for 20 minutes until uniform. Add TEA catalyst, RUB610 toughening agent, and boehmite particles and continue stirring for 40 minutes.
[0041] Homogenization: Use a disperser at 3500 rpm for 20 minutes.
[0042] Coating process on the positive electrode sheet: Degassing: vacuum degassing for 25 minutes (-0.15 MPa).
[0043] Coating and curing: The coating thickness is controlled at 18 μm; first maintain at 70°C for 10 seconds, then cure at a set temperature of 155°C for 40 seconds.
[0044] Example 3: Raw material composition: Main chain polymer: polyadipic acid-ethylene glycol polyol (PAEG, molecular weight 1000): 25 parts by mass; polyethylene oxide (PEO, molecular weight 1500): 10 parts by mass; Cross-linking agent: 4,4'-diphenylmethane diisocyanate (MDI): 10 parts by mass; 1,4-cyclohexyl diisocyanate (CHDI): 5 parts by mass; Catalyst: zinc dilaurate (ZDBC): 0.2 parts by mass; Toughening agent: amino-modified liquid nitrile rubber (Hypro 1300X31, Huntsman): 3.8 parts by mass; Ceramic particles: boehmite particles (D50 = 0.5 μm, Qixian New Materials): 5 parts by mass; Solvent: NMP: 41 parts by mass.
[0045] Preparation process of edge coating: Prepare the mixture: Dissolve PAEG and PEO in NMP and stir in a 40°C water bath for 40 minutes. Add MDI and CHDI and stir for 15 minutes until uniform. Add ZDBC catalyst, ATBN toughening agent, and boehmite particles and continue stirring for 20 minutes.
[0046] Homogenization: Use a high shear dispersing device at 4000 rpm for 10 minutes.
[0047] Coating process on the positive electrode sheet: Degassing: vacuum degassing for 15 minutes (-0.12 MPa).
[0048] Coating and curing: The coating thickness is controlled at 12-15 μm; first maintain at 70°C for 10 seconds, then cure at 150°C for 50 seconds.
[0049] The inventors applied the edge-coating adhesive obtained in each example to the positive electrode sheet and measured the coating's performance, as shown in Table 1. All tests were performed using conventional testing methods. The inventors also conducted comparative tests using a conventional PVDF edge-coating adhesive (Kynar® 6507, Arkema) and a commonly used coating method. Three parallel experiments were conducted, designated Comparative Examples 1, 2, and 3.
[0050] Table 1
[0051] As shown in Table 1, the adhesion and mechanical strength of each embodiment are significantly improved compared to conventional PVDF edge coating, reflecting the good toughness of the present invention. In particular, the thickness change rate during electrolyte immersion is significantly reduced, and the coating uniformity is also better than that of conventional PVDF edge coating.
[0052] The inventors further studied the effect of the distribution ratio of each component in the polymer system on the performance of the edge coating, specifically: Comparative Example 4: Compared with Example 1, the difference is that the main chain polymer contains polytetrahydrofuran (PTHF, molecular weight 1000): 10 parts by mass; polyethylene glycol (PEG, molecular weight 2000): 5 parts by mass, and the rest of the formula is the same as that of Example 1.
[0053] Comparative Example 5: Compared with Example 1, the difference is that the main chain polymer contains 50 parts by mass of polytetrahydrofuran (PTHF, molecular weight 1000) and 10 parts by mass of polyethylene glycol (PEG, molecular weight 2000). The rest of the formula is the same as that of Example 1.
[0054] The edge coating adhesives obtained in Comparative Examples 4 and 5 were subjected to a coating flexibility test, a sag rate during coating, adhesion (peel strength), and mechanical strength (tensile strength). The results are shown in Table 2.
[0055] Table 2
[0056] As shown in Table 2, the quality of the backbone polymer in the polymer system significantly affects the flexibility of the edge coating and the uniformity of the coating process. When the backbone polymer content is too low, the crosslinking system is insufficient to form a continuous film, resulting in a brittle coating with poor flexibility. When the backbone polymer content is too high, the slurry viscosity increases, the coating stability deteriorates, sagging is obvious, and the adhesion and mechanical strength are inferior to those of Example 1. These experimental data verify the rationality of the formulation range.
[0057] Comparative Example 6: Compared with Example 1, the difference is that the cross-linking agent isophorone diisocyanate (IPDI) is 3 parts by mass; the rest of the formula is the same as that of Example 1.
[0058] Comparative Example 7: Compared with Example 1, the difference is that the cross-linking agent isophorone diisocyanate (IPDI) is 20 parts by mass; the rest of the formula is the same as that of Example 1.
[0059] The adhesion (peel strength), mechanical strength (tensile strength), and electrolyte resistance (thickness change rate after immersion in electrolyte) of the obtained edge coating adhesive were measured. The results are shown in Table 3.
[0060] Table 3
[0061] As shown in Table 3, when the crosslinker content in Comparative Example 6 is low, the crosslinking density is insufficient, resulting in a significant decrease in adhesion and mechanical strength, and the coating easily swells after immersion in the electrolyte. When the crosslinker content in Comparative Example 7 is high, although the mechanical strength and electrolyte resistance are slightly improved, the system cost and the risk of residual volatile isocyanate solvent (residual solvent may negatively affect the electrochemical performance of the battery) increase, which is detrimental to environmental and operational safety, and the overall performance is inferior to Example 1. In contrast, Example 1 is the best in terms of mechanical strength, adhesion, electrolyte resistance, cost, and solvent safety.
[0062] Comparative Example 8: Compared with Example 2, the difference is that the ceramic particles: boehmite particles (D50=1 μm): 1 part by mass, and the rest of the formula is the same as that of Example 2.
[0063] Comparative Example 9: Compared with Example 2, the difference is that the ceramic particles: boehmite particles (D50=1 μm): 15 parts by mass, and the rest of the formula is the same as that of Example 2.
[0064] The heat resistance, volume conductivity, coating uniformity, adhesion, mechanical strength, and electrolyte resistance of the obtained edge coating adhesive were measured. The results are shown in Table 4.
[0065] Table 4
[0066] As shown in Table 4, when the ceramic particle content in Comparative Example 8 is low, the heat resistance and electrical insulation of the coating are significantly reduced, and the surface morphology quality is reduced. The adhesion, mechanical strength, and electrolyte resistance are not much different from those in Example 2. When the ceramic particle content in Comparative Example 9 is high, although the heat resistance is slightly improved, the agglomeration of the particles leads to a deterioration of the coating uniformity, while increasing the difficulty of production. The adhesion, mechanical strength, and electrolyte resistance are all undetectable. Based on the above, the ceramic particle content in the embodiment is optimal for the adhesion, mechanical strength, electrolyte resistance, heat resistance, and electrical insulation of the coating.
[0067] In summary, the present invention optimizes the content of each component based on the performance requirements of the edge coating, and achieves excellent adhesion, mechanical strength, electrolyte resistance and coating uniformity through a high-density cross-linked network structure.
[0068] This invention addresses the issues of insufficient adhesion, low mechanical strength, poor electrolyte resistance, and poor coating uniformity in existing edge coating materials. By providing a polymer system based on a hydroxyl-isocyanate crosslinking reaction that rapidly crosslinks and cures (within 60 seconds), this system significantly improves the coating's adhesion, mechanical strength, electrolyte resistance, and coating uniformity, while achieving a highly efficient production process. This provides an innovative solution for high-performance edge coatings for lithium-ion battery positive electrode sheets.
[0069] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A side coating glue for lithium battery positive electrode sheet, characterized in that: The method comprises the following components: main chain polymer, cross-linking agent, catalyst, toughening agent, ceramic particles and solvent; The main chain polymer is a polymer containing a hydroxyl group, and the cross-linking agent is an isocyanate cross-linking agent.
2. The edge coating glue for lithium battery positive electrode sheet according to claim 1, characterized in that: The mass ratio of the main chain polymer, cross-linking agent, catalyst, toughening agent, ceramic particles and solvent is (20-40): (5-15): (0.1-0.5): (1-5): (2-10): (40-60).
3. The edge coating glue for lithium battery positive electrode sheet according to claim 1, characterized in that: The main chain polymer is a mixture of one or more of polytetrahydrofuran, polyethylene glycol, polypropylene glycol, polytetrahydrocarbinol ether, terpolymer polyether, polypropylene oxide, polyethylene oxide, polycaprolactone polyol, polyadipic acid-ethylene glycol polyol, polyethylene oxide, and polytetramethylene oxide.
4. The edge coating glue for lithium battery positive electrode sheet according to claim 1, characterized in that: The crosslinking agent is a mixture of one or more of 1,6-hexamethylene diisocyanate, isophorone diisocyanate, dodecahydrotoluene diisocyanate, 1,4-butanediisocyanate, 2,2,4-trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexyl diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate, and PAPI.
5. The edge coating adhesive for lithium battery positive electrode sheet according to claim 1, characterized in that: The catalyst is any one of dibutyltin dilaurate, zinc octoate, zinc dilaurate, zinc acetylacetonate, tetrabutyl titanate, bismuth trilaurate, zirconium acetylacetonate, triethylenediamine, triethylenediamine, N-methylimidazole, triethyl phosphate, potassium formate, sodium acetate, and bismuth-zinc composite catalyst. And / or, the toughening agent is any one of SR610, ATBN, and CTBN.
6. The edge coating glue for lithium battery positive electrode sheet according to claim 1, characterized in that: The ceramic particles are boehmite particles, and the D50 of the particles is 0.5-5 μm; And / or, the solvent is N-methylpyrrolidone.
7. The method for preparing an edge coating adhesive for a lithium battery positive electrode sheet according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Mix the main chain polymer and solvent according to the ratio and stir evenly; (2) adding a cross-linking agent to the product of step (1) and stirring evenly; (3) Adding a catalyst, a toughening agent, and ceramic particles to the product of step (2) and stirring evenly; (4) Mixing and homogenization.
8. The method for preparing an edge coating adhesive for a lithium battery positive electrode sheet according to claim 7, wherein: During the mixing and homogenization in step (4), the dispersion speed is controlled at 3000 ~ 5000 rpm and lasts for 5 ~ 20 minutes.
9. The use of the edge coating glue according to any one of claims 1 to 6, characterized in that: Used to coat the edge of the positive electrode sheet of a lithium battery. The coating process is as follows: evenly coating the slurry on the edge of the positive electrode sheet; transferring the coated electrode sheet to a hot air circulation oven; Heating step by step: First cure at 60℃-80℃, then heat to curing temperature 150℃-160℃, and the curing time is less than or equal to 60 seconds.
10. The use of the edge coating glue according to claim 9, characterized in that: Before coating, vacuum degas the edge glue slurry: treat the slurry in a vacuum degasser for 15 to 30 minutes, with the pressure controlled at -0.1 to -0.2 MPa to remove bubbles in the slurry; And / or, the positive electrode sheet is subjected to surface pretreatment before coating, wherein the surface pretreatment is surface roughening or plasma treatment.
11. A lithium-ion battery, characterized in that: The positive electrode sheet is coated with the edge coating glue as described in any one of claims 1 to 6.